2009
DOI: 10.1021/jm8014537
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of (R)-6-Cyclopentyl-6-(2-(2,6-diethylpyridin-4-yl)ethyl)-3-((5,7-dimethyl-[1,2,4]triazolo[1,5-a]pyrimidin-2-yl)methyl)-4-hydroxy-5,6-dihydropyran-2-one (PF-00868554) as a Potent and Orally Available Hepatitis C Virus Polymerase Inhibitor

Abstract: The HCV RNA-dependent RNA polymerase has emerged as one of the key targets for novel anti-HCV therapy development. Herein, we report the optimization of the dihydropyrone series inhibitors to improve compound aqueous solubility and reduce CYP2D6 inhibition, which led to the discovery of compound 24 (PF-00868554). Compound 24 is a potent and selective HCV polymerase inhibitor with a favorable pharmacokinetic profile and has recently entered a phase II clinical evaluation in patients with genotype 1 HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 15 publications
0
92
0
Order By: Relevance
“…Filibuvir, also known as PF-00868554 (Fig. 1A), is a member of the dihydroxyprone class of compounds that was identified by a highthroughput screen and dihydroxyprone-based drug design efforts (26). Results from clinical phase 1b trial showed that filibuvir potently decreased viral RNA accumulation in a dose-dependent manner (http://clinicaltrials.gov/ct2/show/NCT00987337).…”
mentioning
confidence: 99%
“…Filibuvir, also known as PF-00868554 (Fig. 1A), is a member of the dihydroxyprone class of compounds that was identified by a highthroughput screen and dihydroxyprone-based drug design efforts (26). Results from clinical phase 1b trial showed that filibuvir potently decreased viral RNA accumulation in a dose-dependent manner (http://clinicaltrials.gov/ct2/show/NCT00987337).…”
mentioning
confidence: 99%
“…The X-ray co-crystal structure of HCV NS5B-PF868554 (PDB ID: 3FRZ) obtained from the RCSB Protein Data Bank (Piscataway, NJ) was used for docking the compounds into the NS5B thumb pocket-II 22 . The protein structure was processed by means of default parameters mentioned in Protein Preparation Tool present in Maestro v9.0 and Impact program v5.5 (Schrödinger, Inc., New York, NY), in which the protonation states of residues were adjusted to the dominant ionic forms at pH 7.4.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…The resulting LigPrep derived structures were used for docking simulations. The X-ray co-crystal structure of HCV NS5B-PF868554 (PDB ID: 3FRZ) was used for docking into thumb pocket-II 22 . Protein refinement without crystallographic water molecules, energy grid generation using bound ligand as a reference, and ''Extra Precision'' (XP) Glide docking v5.0 (Schrödinger, Inc., New York, NY) was performed with the default parameters.…”
Section: Docking Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Another natural compound was erysenegalensein C (Fig. 1) which has been extracted from the bark of Erythrina senegalensis and found probable use in the treatment of stomach pain, female infertility and gonorrhea 26 . manipulations.…”
Section: Introductionmentioning
confidence: 99%